PAYMENT OF MODELS FOR STUDENTS IN SMP NEGERI 7 KELURAHAN PURNAMA KECAMATAN DUMAI BARAT KOTA DUMAI - Samsiah "; Ahmad Hidir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted in SMP Negeri 7 Kelurahan Purnama Kecamatan Dumai Barat Kota Dumai. The purpose of this study is to analyze the use of pocket money by Students / I SMP Negeri 7 Kelurahan Purnama Kecamatan Dumai Barat Kota Dumai. The focus of this study is the pattern of giving pocket money to students / I in SMP Negeri 7 Kelurahan Purnama Kecamatan Dumai Barat Kota Dumai. The sample in this study amounted to 72 students using slovin method from students who sat in class VIII SMP Negeri 7 Kelurahan Purnama Kecamatan Dumai Barat Kota Dumai. The writer uses quantitative descriptive method and the data is analyzed quantitatively and using the technique of Simple Random Sampling. Data instruments are observation, questionnaire/ questionnaire and documentation. From the research conducted, the authors found that the pattern of giving pocket money by parents to students in SMP N 07 Purnama is as follows: Per day, Students who get snack every day amounted to 58 students or 80.5% of respondents. Week, Students who get snack per week amounted to 11 students or 15.27% of respondents.Monthly, Students who get snack per month amounted to 3 students or 4.1% of respondents. The use of pocket money by the students of SMP N 07 Purnama is as follows: For pocket money, the use of allowance for snack by students of SMP N 07 Purnama on the research conducted found 30 students or 41.7% of respondents. For school purposes, the use of allowance for school purposes by students of SMP N 07 Purnama on research conducted found as many as 8 students / i or 11.1% of respondents. To save, the use of allowance to save by students of SMP N 07 Purnama on research conducted found as many as 6 students / i or 8.3% of respondents. To purchase internet quota / card, The use of allowance for internet quota by students of SMP N 07 Purnama on research conducted found as many as 3 students / i or 4.2% of respondents. For transportation costs, the use of allowance for transportation costs by students of SMP N 07 Purnama in research conducted found as many as 25 students / i or 34.7% of respondentsKeywords: Child Pocket Money Pattern, Expenditure Pattern